2020
DOI: 10.1038/s41398-020-00935-x
|View full text |Cite
|
Sign up to set email alerts
|

Nedd4l downregulation of NRG1 in the mPFC induces depression-like behaviour in CSDS mice

Abstract: The occurrence of major depressive disorders has been closely related to the vulnerability of stress. The medial prefrontal cortex (mPFC) is involved in regulating pathological reactivity to stress, changes in affective behaviour and cognitive functions by distress. Increasing evidence indicates that neuregulin 1 (NRG1) plays an important role in psychiatric illnesses, including depression, schizophrenia and bipolar disorder. However, whether NRG1 in the mPFC is related to stress vulnerability remains unclear.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 42 publications
(51 reference statements)
1
6
0
Order By: Relevance
“…NRG1 promotes hippocampal long-term depression induction in adult mice [ 52 ]. Nedd4l-mediated downregulation of NRG1 in the medial prefrontal cortex induced depression-like phenotypes mice in chronic social defeat stress [ 53 ]. Moreover, NRG1 plays a vital role in the development and plasticity of the brain.…”
Section: Discussionmentioning
confidence: 99%
“…NRG1 promotes hippocampal long-term depression induction in adult mice [ 52 ]. Nedd4l-mediated downregulation of NRG1 in the medial prefrontal cortex induced depression-like phenotypes mice in chronic social defeat stress [ 53 ]. Moreover, NRG1 plays a vital role in the development and plasticity of the brain.…”
Section: Discussionmentioning
confidence: 99%
“…Animals under pathophysiological conditions usually have impaired motor functions and a longer duration of immobility. Previous studies have demonstrated that exposure to LPS or CSDS contributes to murine depression‐like behavior accompanied by the suppression of motor activity (Xu et al., 2020 ; Zhang et al., 2019 ). The LPS‐induced model of inflammation and the CSDS model are widely for studying the neurobiological mechanisms of depression.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that adverse factors during stress lead to permanent changes in genes. These changes in genes result in raised risk coefficient of depression, diabetes, Alzheimer’s disease, hypertension, and cardiovascular disease ( Graham and Smith, 2016 ; Sartorius, 2018 ; Harshfield et al, 2020 ; Xu et al, 2020 ). A recent study suggested that stress markedly increased glucose content both in the blood and brain structures ( Detka et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%